Characterization of GH, GHR and IGF-I in Broiler Lines Selected for Rapid Growth or Improved Feed Efficiency - Rahimi, G. (International Journal of Poultry Science, 2005)
The aim of this study was to figure out the response of the GH axis to selection criteria in broiler chickens. Plasma profiles of GH, IGF-I along with membrane GHR binding activity were examined during rapid growth phase in experimental lines of broiler chickens. The selection criteria applied influenced the plasma GH levels and the number of hepatic GHR. There was a higher plasma GH level in FC chickens compared to GL chickens while the opposite pattern was observed for GHR. The negative correlation between plasma GH levels and hepatic GHR suggest a down regulatory mechanism for GHR in broiler chickens. The absence of line differences in plasma IGF-I levels between GL and FC lines in spite of clear difference in growth rate and in plasma GH concentrations may support the concept that plasma IGF-I does not appear to be GH-dependent, implying the importance of other factors besides GH in the regulation of IGF-I in chickens. The slower growth rate as function of time in the FC line during rapid growth phase was followed by a phase of compensatory growth. On the basis of this growth curve pattern it can be hypothesized that the dynamics of GH action are shifted or extended to the phase of compensatory growth as an effect of the selection on feed conversion. This may be a causal mechanism for the different growth curve pattern in GL and FC lines. Assuming that the metabolic basis for these differences is better understood it may be possible to device other procedures for improving meat quality in poultry industry.